Intravoxel incoherent motion imaging predicts exercise‐based rehabilitation response in individuals with low back pain. (29th July 2021) - Shahidi, Bahar; Behun, John J.; Berry, David B.; Raiszadeh, Kamshad; Englund, Erin K.
Abstract : Exercises to strengthen and stabilize the trunk musculature are a common conservative treatment strategy for low back pain (LBP), despite the possible presence of impairments in muscle activation in this population. Intravoxel incoherent motion (IVIM) MRI permits evaluation of activation‐induced blood flow through diffusion‐weighted images that are sensitized to microvascular blood flow. In the current study we aimed to evaluate IVIM signal changes after exercise in patients with LBP compared with pain‐free healthy controls and determine if these changes were related to reductions in disability with a 12‐week rehabilitation program. We hypothesize that the magnitude of changes in IVIM parameters in the lumbar extensor muscles will be smaller in patients with LBP compared with those without LBP, and that these magnitudes will be correlated with responsiveness to a 12‐week, resistance‐based exercise program. IVIM MR data for molecular diffusion (D), blood flow pseudodiffusion (D*) and perfusion fraction (f) were collected before and immediately after an ~ 3‐min session of high‐intensity lumbar extension resistance exercise in 16 healthy participants and 17 participants with LBP. Improvements in LBP‐related disability after the 12‐week, machine‐based, high‐intensity exercise rehabilitation program were measured in the LBP group. We observed a significant increase in all IVIM parameters (f, D*, D) in response to exercise ( p  < 0.0001) and an interaction of group‐by‐time for D ( p  = 0.016). Thresholds were identified using receiver operating characteristic (ROC) curves for diffusion and pseudodiffusion coefficients, which predicted a reduction in LBP‐related disability in response to the 12‐week, exercise‐based rehabilitation program. Exercise was associated with an increase in (f), capillary blood flow‐based pseudodiffusion (D*) and diffusion coefficient (D), regardless of the presence of LBP. Additionally, subgroup analysis identified patients who were not responsive to the acute exercise session, for whom, based on ROC analysis, there was no clinically significant change in disability following the 12‐week program. Abstract : Intravoxel incoherent motion imaging allows for evaluation of muscle perfusion changes in response to exercise. This technique identified individuals with low back pain who did not respond to a 12‐week, exercise‐based rehabilitation program. This may be a valuable tool for improved patient selection for conservative management.